Inequidad y precariedad laboral de la mujer en la inserción al mercado laboral en empresas del sector privado en Colombia (2021)
Discrimination against women in the labor sector and their low presence in the labor market, together with the problems of the burdens associated with the domestic work, contexts of gender violence and another series of inequalities of gender, constitute strong barriers for them to actively participate in the economically productive spaces, added to the predisposition that the entrepreneurs towards women, in relation to maternity situations that are claim as the sole responsibility of the woman (Maternity leave, school subjects of boys and girls, illness of boys and girls, among others).